A non-axisymmetric temperature field reconstruction method based on the interferometric fringe schlieren method. (1st April 2023) - Wu, Jun; Pan, Zhixiang; Zhang, Chenping; Song, Fengcheng; Zhang, Xiaoyu; Guo, Runxia
Abstract: The typical non-axisymmetric temperature field distribution in the tail nozzle outlet area of the combustion chamber of an aircraft engine can reflect the operating state of the engine. As an effective non-contact method for measuring a non-axisymmetric temperature field, the traditional background-oriented schlieren (BOS) method has the problem that the extraction accuracy of light deflection is not high. In this paper, interference fringes are introduced into the schlieren measurement, and the highly sensitive fringe offset replaces the traditional background speckle offset for measurement, which realizes accurate reconstruction of the non-axisymmetric temperature field. Firstly, through the interferometric fringe schlieren (IFS) method comprising multiple sets of double-slit interferometric systems and imaging sensors, the offset of the interference fringe after passing through the non-axisymmetric temperature field is measured by image processing. The spatial refractive index field is then reconstructed by the filtered back-projection algorithm under the sector model proposed in this paper and the spatial temperature field is obtained. The experimental results show that the temperature field reconstruction error is smaller for the IFS method than the BOS method, the measurement area is accurate from 0.5 mm for the BOS method to 0.2 mm for the IFS method and the temperature error range is reduced from 50 K for the BOS method to 25 K for the IFS method.